Commentary on Gender Differences in Prevalence, Treatment, and Quality of Life of Patients with Chronic Rhinosinusitis. Issue 2 (June 2015) - Ference, Elisabeth H.; Tan, Bruce K.; Hulse, Kathryn E.; Chandra, Rakesh K.; Smith, Sean B.; Kern, Robert C.; Conley, David B.; Smith, Stephanie Shintani
Objective: To examine the existing evidence on gender differences in the prevalence, treatment, and quality of life of patients with chronic rhinosinusitis (CRS). Methods: Review of the literature and expert opinion. Results: From a sociologic standpoint, women have historically been considered more likely to report symptoms, seek medical care, and give poorer self-evaluation of health, which may bias data toward increased prevalence and a greater effect of CRS on quality of life in women. However, the influence of gender seems to be restricted primarily to the evaluation of general quality of life, whereas the disease-specific health-related quality of life is not different between genders. Furthermore, migraine headaches, which are more common among women, may be misdiagnosed as CRS, which contributes to gender differences in the prevalence of CRS. The degree to which reported differences in prevalence and health utilization represent biologic or physiologic differences between genders is not known; however, differences in anatomic size, tobacco susceptibility, and hormonal factors have been speculated to increase the overall susceptibility to CRS in women compared with men. Conclusions: Focused research that examines the effect of gender on the development, treatment, and outcomes of CRS is warranted.